Music as Identity: The Dynamics of the Pop Punk Community in Bojonegoro from a Subcultural Perspective - Maharani, Natahsya; Arief, Sudrajat (Paradigma, 2025)
Abstrak This study examines the pop punk scene community in Bojonegoro Regency as a subcultural phenomenon developing in a non-metropolitan context. The research focuses on how pop punk music is used as a medium for expressing subcultural identity through music, lifestyle, and cultural symbols amid the dominance of mainstream culture. Employing a qualitative approach with a case study method grounded in the constructivist paradigm, data were collected through in-depth interviews, participant observation, and documentation involving members of the Bojonegoro Pop Punk community. Data analysis was conducted using Miles and Huberman’s interactive model, supported by Dick Hebdige’s subculture theory and Alberto Melucci’s theory of collective identity. The findings indicate that the subcultural identity of the pop punk community is constructed through three main dimensions: music as a medium for articulating emotional distress and emotional release through punk pop bricolage practices; lifestyle and visual style as symbolic markers that distinguish the community from dominant culture; and cultural symbols such as logos, merchandise, and gigs as mechanisms for reinforcing collective identity and internal solidarity. Community solidarity functions as a defensive mechanism against social stigma through passive and productive forms of resistance centered on creative practices. This study concludes that the pop punk scene in Bojonegoro operates not only as a music community but also as an alternative social space for young people to construct identity, solidarity, and symbolic resistance within a non-metropolitan local context. Keywords: Pop punk, Subculture